Lithocarpus pacoensis (Fagaceae) a new species from Hoa Binh Province, Vietnam - Nguyen Van, Ngoc; Hoang, Son Thanh; Hoang, Binh Thi (VNU Journal of Science: Natural Sciences and Technology, 2022)
Lithocarpus pacoensis Ngoc & Son from Hoa Binh province, Northern Vietnam, is described her e and illustrated. The new species is  most  similar to Lithocarpus komtumensis A.Camus and Lithocarpus laoticus (Hickel & A.Camus) A.Camus in having long petioles; big cupules, usually clustered in sets of three, flat apical , nearly completely enclosing the nut ; nut subglobose apex rounded or flat; scar covering 2/3 to most of the nut, convex. But the new species significantly differs from L. kontumensis and L. laoticus in having bigger leaf blades, longer petiole, much bigger cupule and nut, much more number of secondary veins, and shorter infructescences . The morphological description , comparison with related species, photographs, and preliminary conservation status descriptions are also provided.